DAMPAK INVESTASI ALIBABA GROUP DI TOKOPEDIA DAN LAZADA TERHADAP PERKEMBANGAN E-COMMERCE DI INDONESIA - Emi Meidila Sidauruk; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research focuses on the impact of market expansion carried out by the Alibaba Group in Indonesia. Alibaba Group Holding Ltd is one of the multinational companies (corporations) that are currently growing rapidly in the field of digital business (e-commerce). Alibaba Group is actively expanding its business to various parts of the world. The European and American regions have successfully become targets for its expansion. Since 2015, Alibaba Group began to expand its business operation network to the Asia-Pacific region. Of all the countries in the Asia-Pacific region, it turns out that Indonesia is the main e-commerce market target. Alibaba makes acquisitions and investments in Indonesia. Alibaba acquired 67% of Lazada and invested US $ 1 billion in Lazada and TokopediaThis research uses library research method with qualitative design. Data and information are obtained through literature review or document analysis (secondary data) based on sources from books, journals, scientific articles, and printed and electronic mass media. This research uses a neoliberal perspective and the Multinational Corporation analysis. It uses Complex Interdependence theory by Robert O Keohane and Joseph S. Ny and Foreign direct Investment theory.Overall, The expansion carried out by Alibaba Group has had a good impact on Tokopedia and the Indonesian e-commerce world. This is proven because Tokopedia is included in the top four e-commerce sites that are most visited every month in the Southeast Asian market. For the e-commerce market in Indonesia all compete with each other to be able to continue to increase the number of sales every day Key Words:Neoliberal, Complex Interdependence, Foreign Direct Investment, E-commerce